Non-Traditional Raw Materials in Pasta Production of High Nutrition Value - Smirnov S.; Fazullina O. (Техника и технология пищевых производств)
The article features the problems of improving the range of pasta products. The quality of food and the overall balance of the human diet are crucial in the state of health and quality of life. Macaroni products are in great demand among all population groups, so it can be considered as an object for the introduction of enriching and functional components. Pasta industry produces scores fortified products with dietary and/or functional orientation, but their percentage remains insignificant. Given the popularity of pasta, it can be a promising direction to include non-traditional raw materials in the pasta dough in order to change its chemical composition and increase nutritional value. The research employed methods of systematization, analysis, and generalization. The research was conducted on the premises of the Scientific Research Institute of Food-Concentrate Industry and Special Food Technology, Branch of Federal Research Center of Nutrition and Biotechnology. The article contains an overview of the scientific works by Russian and foreign researchers on improving the range of pasta products, namely pasta with functional properties, using non-traditional raw materials. It also describes some ways of expanding the use of existing raw materials, new formulations and technologies for the production of functional pasta with non-traditional raw materials. The research revealed some problems and trends in the pasta industry. The study is of theoretical importance and can be useful for scientists and producers in the development of new formulations and/or technologies of pasta with desired functional properties using non-traditional raw materials.